Eleven undocumented Firefox tips. - Spector, Lincoln
Don;t like the way Firefox works? Then change it! The alternative browser offers plenty of ways to customize. Here are some great tweaks that you might not know about.
Keywords: Firefox; Browsers (Computer programs)